2018
DOI: 10.1007/s12010-017-2681-3
|View full text |Cite
|
Sign up to set email alerts
|

Substituting Both the N-Terminal and “Cord” Regions of a Xylanase from Aspergillus oryzae to Improve Its Temperature Characteristics

Abstract: To improve the temperature characteristics of AoXyn11A, a mesophilic glycoside hydrolase family (GHF) 11 xylanase from Aspergillus oryzae CICC40186, its N-terminal and "cord" regions were selected to be substituted by means of the computer-aided analysis and calculation. In brief, one mutant, named ATX11A, possessing the lowest root-mean-square deviation (RMSD) value was designed based on the molecular dynamics (MD) simulation by substituting the N-terminal 41 amino acids of AoXyn11A with the corresponding 42 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 32 publications
1
4
0
Order By: Relevance
“…Compared to Mtxylan2, 28N, 28C, and 28NC showed 2.4-fold, 4.1-fold, and 9.3-fold higher specific activities for beechwood xylan, 7.1-fold, 26.7-fold, and 10.4-fold higher specific activities for birchwood xylan, and 4.5-fold, 13.4-fold, and 7.9-fold higher specific activities for oat spelling, respectively ( Table 1 ). These results suggested that truncation of the N-terminus, C-terminus, and both the N-terminus and C-terminus of Mtxylan2 enhanced its specific enzyme activity, which was in agreement with the findings of Kang and Ishikawa (2007) , Li et al (2018) , Liu et al (2011) and Pan et al (2022) . The kinetic parameters of the enzymes with beechwood xylan are listed in Table 2 .…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…Compared to Mtxylan2, 28N, 28C, and 28NC showed 2.4-fold, 4.1-fold, and 9.3-fold higher specific activities for beechwood xylan, 7.1-fold, 26.7-fold, and 10.4-fold higher specific activities for birchwood xylan, and 4.5-fold, 13.4-fold, and 7.9-fold higher specific activities for oat spelling, respectively ( Table 1 ). These results suggested that truncation of the N-terminus, C-terminus, and both the N-terminus and C-terminus of Mtxylan2 enhanced its specific enzyme activity, which was in agreement with the findings of Kang and Ishikawa (2007) , Li et al (2018) , Liu et al (2011) and Pan et al (2022) . The kinetic parameters of the enzymes with beechwood xylan are listed in Table 2 .…”
Section: Resultssupporting
confidence: 89%
“…Among them, GH11 xylanase has a conserved β-jelly roll structure with a right-handed partially closed conformation ( Paes et al, 2012 ). GH11 xylanase has a small molecular weight, fast catalytic efficiency, and excellent substrate selectivity ( Li C. et al, 2018 ; Teng et al, 2019 ; Wang et al, 2021 ). These properties make GH11 xylanase promising for a wide range of applications in industries such as animal feeding, food baking, and pulp bleaching.…”
Section: Introductionmentioning
confidence: 99%
“…The flexibility of the GH11 xylanase N-terminus is closely associated with its thermal stability . Rigidification of the flexible regions of xylanase, particularly the N-terminus, is an effective strategy to improve thermostability. In the present study, MD simulations and multiple sequence alignments were used to localize five loop regions with greater flexibility in the N-terminus of S. rameus L2001 xylanase XynA, comprising loop1- 5 TTN 7 , loop2- 11 TDNGFY 16 , loop3- 23 AQ 24 , loop4- 32 GS 33 and S 36 , and loop5- 42 RNT 44 (Figure ).…”
Section: Discussionmentioning
confidence: 99%
“…Xylanase or endo-1,4-beta-xylanase (EC 3.2.1.8) is a group of enzyme which plays a crucial role in the xylan hydrolysis, the most common natural hemicellulose, into short oligosacharides and xylose (He et al, 2015), (Li et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the species A. oryzae is a potential target of scientific researches around the world (Chipeta et al, 2005), (Golubev et al, 1993), (He et al, 2015), (Kimura et al, 2000). Besides the advantages of production of xylanase with high activity, xylanase produced from A. oryzae has some outstanding features such as specific structural regions which we can use mutation techniques, recombinant proteins, the catalyst… to significantly increases catalytic efficiency and heat resistance (Gao et al, 2012), (Li et al, 2018), Li et al, 2017).…”
Section: Introductionmentioning
confidence: 99%